2002
DOI: 10.1002/jnr.10148
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective actions of selegiline

Abstract: Selegiline, a selective inhibitor of monoamine oxidase-B (MAO-B), was one of the first adjunct therapies in clinical neurology. A retrospective analysis of data from patients with Parkinson's disease found a significant increase in survival in those treated with selegiline plus L-dopa compared with L-dopa alone. The mechanism of action of selegiline is complex and cannot be explained solely by its MAO-B inhibitory action. Pretreatment with selegiline can protect neurons against a variety of neurotoxins, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(64 citation statements)
references
References 31 publications
3
61
0
Order By: Relevance
“…Within the dentate gyrus, immunohistochemical procedures revealed the polysialylated cells to be located specifically at the infragranular zone with a well-established dendritic arbor extending through the granule cell zone and into the overlying molecular layer (Figure 3). Nefiracetam, a well-established nöotrope (Shorvon, 2001) and the neuroprotective drug deprenyl (Ebadi et al, 2002) were employed to determine if increased dentate polysialylated cell frequency followed chronic administration of other agents that enhance acetylcholine and memory function. Nefiracetam exhibited an action very similar to that observed with tacrine.…”
Section: Effect Of Chronic Drug Treatment or Complex Environment Rearmentioning
confidence: 99%
“…Within the dentate gyrus, immunohistochemical procedures revealed the polysialylated cells to be located specifically at the infragranular zone with a well-established dendritic arbor extending through the granule cell zone and into the overlying molecular layer (Figure 3). Nefiracetam, a well-established nöotrope (Shorvon, 2001) and the neuroprotective drug deprenyl (Ebadi et al, 2002) were employed to determine if increased dentate polysialylated cell frequency followed chronic administration of other agents that enhance acetylcholine and memory function. Nefiracetam exhibited an action very similar to that observed with tacrine.…”
Section: Effect Of Chronic Drug Treatment or Complex Environment Rearmentioning
confidence: 99%
“…Despite considerable progress in understanding the interactions of the two enzyme forms with their preferred substrates and inhibitors, no general rules are yet available for the rational design of potent and selective inhibitors of MAO possibly due to the fact that the mechanism of interaction of the new drugs with MAO isoforms have not been fully characterized. Preferential MAO-A inhibitors have been recognized as therapeutically useful antidepressants while MAO-B inhibitors have been found to be beneficial in the treatment of Parkinson's disease and Alzheimer [18,19,20] . Bellik L.etal [21] , reported that the novel MAO-B inhibitor PF9601N, its cytochrome P450-dependent metabolite FA72 and l-deprenyl were studied as potential peroxynitrite (ONOO) scavengers and nitric oxide synthase (NOS) inhibitors both the novel MAO-B inhibitor as well as its metabolite were able to strongly inhibit rat brain neuronal NOS (IC50 of 183 μM and 192 μM, respectively), while l-deprenyl at the highest concentration used (3 mM), caused only a slight decrease of the enzyme activity.…”
Section: Resultsmentioning
confidence: 99%
“…In order to preserve brain dopamine, it is also common to treat patients with a monoamine oxidase B (MAO-B) inhibitor. 4 Selegiline (L-Deprenyl) and Rasagiline ( Figure 1) [5][6][7][8][9][10] are selective inhibitors of MAO-B and Selegiline is currently used for the treatment of Parkinson's and Alzheimer's diseases. This compound was reported to have a neuroprotective activity due to the prevention of apoptosis.…”
Section: 3mentioning
confidence: 99%